The Impact Of COVID-19, Media Relations, And Entrepreneurship Education On Financial Performance Of Online Service Companies - Irawan, Rizka; Ismiyati, Defifi (STAI Denpasar Bali, 2023)
This research aims to investigate the influence of the COVID-19 pandemic, media relations strategies, corporate branding, communication styles, and entrepreneurship education on the financial performance of online service companies amidst turbulent market conditions. The study adopts a mixed-methods approach, utilizing in-depth interviews and content analysis. Sampling will target a diverse range of online service companies, focusing on those operating in sectors heavily impacted by the pandemic. Data analysis will involve thematic coding to identify key factors shaping financial performance. Findings will shed light on the interplay between external factors, communication strategies, and entrepreneurship education in navigating challenging market landscapes, providing insights for both academia and industry.